RISK FACTORS FOR PULMONARY TUBERCULOSIS COINFECTION IN HIV/AIDS PATIENTS - Ildha Rosendy Kurnianda; Apriliana, Ety; Putri, Giska Tri; Wardani, Dyah Wulan Sumekar Rengganis (Medula, 2025)
Tuberculosis and HIV co-infection is a major public health problem in many parts of the world. In Indonesia, tuberculosis (TB) is an opportunistic infection that most often occurs in people living with HIV/AIDS (PLWHA). HIV infection increases susceptibility to Mycobacterium tuberculosis, thereby increasing the risk of developing TB. The World Health Organization (WHO) estimates that TB causes 13% of deaths in AIDS sufferers. Tuberculosis (TB) and HIV co-infection occurs when a person is infected with Mycobacterium tuberculosis and HIV at the same time. People with HIV have a 30 times greater risk of suffering from TB than people who are not infected with HIV. There is a significant relationship between these two infections, where each infection accelerates the development of the other infection. HIV infection can trigger reactivation of latent TB into active TB, while TB infection can worsen the clinical condition of patients who have been infected with HIV. The aim of this study was to determine various risk factors for pulmonary tuberculosis co-infection in HIV/AIDS patients. The method used is qualitative with literature study as a data collection technique. The results obtained were alcohol consumption and extra-pulmonary TB, education level, monthly income, occupation, family history of PTB, lack of appetite, balanced diet, maintaining healthy nutrition, smoking, and stopping taking medication if you felt the condition was under control and the incidence of PTB were factors associated with an increase in pulmonary tuberculosis co-infection..